The Effect of Coping Strategies on the Dietary Regulation of Patients with Hypertension - Fikriana, Riza; Nursalam2, Nursalam; Devy, Shrimarti Rukmini; Ahsan, Ahsan; Afik, Al (International Journal of Psychosocial Rehabilitation, 2020)
Dietary regulation in patients with hypertension is an important component of hypertension management to control their blood pressure and to prevent complications. This study aims to analyze the effect of coping strategies on the dietary regulation of patients with hypertension. The study employed an analytical observational design with a cross-sectional approach. The research was conducted in Malang regency, Indonesia. As many as 225 second and third levels of hypertension sufferers have been used as the sample of this study. The samples were taken using multistage random sampling. The variables of the study came in the form of focused coping inclusive of active coping, planning, restraint, the suppression of competing activities, seeking informational and instrumental social support and emotion-focused coping that consists of positive reinterpretation, turning to religion and seeking emotional social support. The study also employed a research instrument in the form of a questionnaire using the Scales of the COPE Inventory and the Hypertension Self-Care Profile 1(HBP SCP). The data was analyzed using linear regression testing. The results show that restraint (p-value=0.021), positive reinterpretation (p- value=0.006), turning to religion (p-value=0.044) and seeking emotional social support (p-value=0.010) significantly influence the dietary regulation of patients with hypertension. Emotion-focused coping has become a more dominant factor when it comes to influencing the dietary regulation of patients with hypertension.